Meta Analysis the Effect of Critical Thinking Skills Towards Students’ Storytelling Skills - Dhika Santhi; Hanip Pujiati; Saifur Rohman (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this study is to evaluate how critical thinking affects students' storytelling skills while they learn English. The findings of previous research will be used to analyze this influence. The meta-analysis method is employed in this study. A meta-analysis examines several research findings on related issues. Written materials about critical thinking research, such as journal articles and research reports that were specifically chosen because they fulfill the research issue, become the analytical unit in this type of study. With the use of a documentation guide, the researcher serves as the primary instrument for this study. Quantitative data analysis using percentages and qualitative data analysis for data derived from narrative studies of the research findings are the methods employed for data analysis. The results of this research showed that teaching English to students through the storytelling approach enhances their capacity for critical thought, decision-making, and narrative invention.